Online Retail Service Quality: Scale Development and Validation. Issue 3 (June 2023) - Swar, Biranchi Narayan; Panda, Rajesh
The growth of online retailing has created an opportunity to create a scale specifically for online retail services. At the same time, the increasing rate of internet penetration in India coupled with electronic banking and wallets has formed new market place for many online retailers. In this context, to gain competitive advantage, the online retailers should provide better service quality. Thus, the present research tries to know the various constructs of retail service quality (RSQ) in online format and develop a measurement scale. The study has borrowed the constructs from 'Retail Service Quality' (RSQ) and 'Technology Acceptance Model' (TAM). For this purpose, we collected data from 600 respondents. The scale has been confirmed and validated by using CFA. The study confirmed that online RSQ (ORSQ) scale consists of four constructs: 'Ease of Use', 'Problem Solving', 'Policy' and 'Reliability' with 18 variables. The article has concluded and validated a scale for ORSQ which can help the online retailers to design their service offering. The implications of the ORSQ scale for practitioners, as well as for future research, are discussed in this article.